2016
DOI: 10.1039/c5md00358j
|View full text |Cite|
|
Sign up to set email alerts
|

Probing substrate binding to the metal binding sites in metallo-β-lactamase L1 during catalysis

Abstract: Metal ions in metallo-β-lactamases (MBLs) play a major role in catalysis. In this study we investigated the role of the metal ions in the Zn1 and Zn2 sites of MBL L1 during catalysis. A ZnCo (with Zn(II) in the invariant Zn1 site and Co(II) in the Zn2 site) analog of MBL L1 was prepared by using a biological incorporation method. Extended X-ray Absorption Fine Structure (EXAFS) spectroscopic studies were used to confirm that the ZnCo analog was prepared. To study the roles of the Zn(II) and Co(II) ions during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The pro -( R ) boron-bound exocyclic oxygen bridges Zn1 and Asp 120 , mimicking the proposed position of the hydroxide-derived oxygen in the oxyanion intermediate. Overall, the complexes of 2 with VIM-2 and BcII reveal that binding of the cyclic boronates closely mimics that proposed for the high-energy tetrahedral intermediate in MBL catalysis 21 ( Fig. 2a,e ), both in terms of structure and bonding.…”
Section: Resultssupporting
confidence: 69%
“…The pro -( R ) boron-bound exocyclic oxygen bridges Zn1 and Asp 120 , mimicking the proposed position of the hydroxide-derived oxygen in the oxyanion intermediate. Overall, the complexes of 2 with VIM-2 and BcII reveal that binding of the cyclic boronates closely mimics that proposed for the high-energy tetrahedral intermediate in MBL catalysis 21 ( Fig. 2a,e ), both in terms of structure and bonding.…”
Section: Resultssupporting
confidence: 69%
“…Such changes in the positioning of metal ions induced by inhibitor–substrate interactions in β-lactamase catalysis have also been observed with extended X-ray absorption fine structure (EXFAS) spectroscopy studies, as shown in the case of the subclass B3 MBL L1 from S. maltophilia and with other metallo-enzymes (see e.g., ); it may also be that the extent of such metal ion translocations is not fully reflected in crystallographic compared to solution studies. It should also be noted that the precipitants used in crystallography experiments for NDM-1: VNRX-5133 and OXA-10: VNRX-5133 structures were at pH 5.8 and pH 8.0, respectively.…”
Section: Resultsmentioning
confidence: 99%
“… a) B3 variants with the canonical HHH/DHH motif. The most studied representatives from the B3 MBL subgroup are L1 from S. maltophilia ( Simm et al, 2002 ; Aitha et al, 2016 ; Kim et al, 2020 ) and AIM-1 from P. aeruginosa ( Selleck et al, 2016 ), with the latter posing a major threat to healthcare due to its high catalytic efficiency towards a broad range of β-lactam antibiotics ( Supplementary Table S1 ). The metal ion in the Zn1 site is tetrahedrally coordinated by the three histidine ligands of the active site motif, as well as the oxygen from the hydroxide that in the resting enzyme bridges the two metal ions and which acts as the nucleophile that initiates the hydrolysis of the β-lactam bond.…”
Section: Discussionmentioning
confidence: 99%